Human Rights Violations in Indonesia’s National Strategic Development Project - Herwati, Siti Rakhma Mary; Wungkana, Pascal David (Indonesian Journal of Law and Society, 2023)
The Indonesian Legal Aid Foundation has identified several typologies of structural land cases. One of them is land cases concerning the development of infrastructure projects. In recent years, the government has intensified particular infrastructure projects by designating them as National Strategic Projects (PSN). The designation of certain locations for these National Strategic Projects often overrules the consent of local communities who will be affected by the project. Some cases of infrastructure project development have occurred and impacted such communities. This paper will explicate how the accelerated development of infrastructure projects through the issuance of the Presidential Regulation on National Strategic Projects in 2016 and 2017 have violated community rights to land, the environment, and other human rights. The author will reveal the violation of these rights through examining cases on the construction of the Bener Dam in Central Java and the development of Bitung Toll Road in North Sulawesi. This paper projects one main finding that the government did not use the right to development approach and public needs-based approach in carrying out the project developments. Violations on a couple cases of development, such as Bener Dam and Bitung Toll Road, strengthen the analysis of governmental arbitrariness on conducting PSN in Wadas and Bitung.